Oil discoveries and democracy - Tania Masi; Roberto Ricciuti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We evaluate the effect of natural resources on political regimes. We use the synthetic control method to compare evolution of the democracy level of countries affected by giant oil discoveries with the weighted democracy level of countries that do not incur the same event and have similar pre-event characteristics. Focusing on 12 countries affected by the peak of oil discovery from the 1970s, we find that the exogenous variation in oil endowment does not have the same effect on all countries. In most of cases, the event has a negative effect in the long run, but countries with a high level of democracy in the pre-event period are not affected by the peak of oil discoveries. These results support heterogeneity and non-linearities claimed in the more recent theoretical literature.
Keywords: C21; C23; O57; P48; 330; natural resources; oil discoveries; democracy; synthetic control method